A rare case of classical Hodgkin's lymphoma in the setting of a newly diagnosed left atrial myxoma. (29th October 2015) - Bolanos, Alexander Javier; Dibu, George; Burke, Floyd W; Klodell, Charles T; Li, Ying; Rand, Kenneth H; Lucas, Alexandra Rose
Abstract : We report a rare case of left atrial myxoma with concomitant classical Hodgkin's lymphoma in a 36-year-old woman with a non-significant medical history and 4 months of progressively worsening palpitations, dyspnoea on exertion, chest discomfort and fatigue. Outpatient echocardiography revealed functional mitral valve stenosis as a result of a large left atrial cardiac mass. Preoperative thoracic imaging revealed an anterior mediastinal mass with associated lymphadenopathy. The patient underwent successful resection of the anterior mediastinal mass and left atrial mass. Surgical pathology revealed myxoma in the left atrium and classical Hodgkin's lymphoma in the anterior mediastinum. Thus the patient was diagnosed with early-stage classical Hodgkin's lymphoma. This clinical vignette emphasises the importance of a comprehensive diagnostic evaluation in the setting of a newly discovered atrial tumour.